2007
DOI: 10.2478/s11686-007-0022-3
|View full text |Cite
|
Sign up to set email alerts
|

Larval Hysterothylacium sp. (Nematoda, Anisakidae) and trematode metacercariae from the amphipod Paracorophium excavatum (Corphiidae) in New Zealand

Abstract: Previously undescribed fourth-stage larvae of anisakid nematodes were found in the haemocoel of the amphipod Paracorophium excavatum (Thomson, 1884) (Corophiidae) in New Zealand. Morphological examination by light microscopy showed that the worms belonged to a species of Hysterothylacium Ward et Magath, 1917, based on several characters including the presence of interlabia, the location of the excretory pore posterior to the nerve ring, and the characteristics of the intestinal caecum and ventricular appendix.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…However, these authors investigated the gastropod mollusc Gundlachia radiata (Guilding, 1828) and identified the larvae as belonging to the Contracaecum genus. Luque et al (2007) recorded the presence of Hysterothylacium larvae in amphipods in New Zealand. However, the prevalence found by Thiengo et al (2000) and Luque et al (2007) were low compared to this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these authors investigated the gastropod mollusc Gundlachia radiata (Guilding, 1828) and identified the larvae as belonging to the Contracaecum genus. Luque et al (2007) recorded the presence of Hysterothylacium larvae in amphipods in New Zealand. However, the prevalence found by Thiengo et al (2000) and Luque et al (2007) were low compared to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Luque et al (2007) recorded the presence of Hysterothylacium larvae in amphipods in New Zealand. However, the prevalence found by Thiengo et al (2000) and Luque et al (2007) were low compared to this study. From the 65 Gundlachia radiata specimens collected, only three were parasitized by Contracaecum larvae and with a maximum intensity of two larvae per host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In common with some other aquatic ascaridoids, species of Hysterothylacium have evolved remarkable flexibility in completing the life-cycle. For example, Luque et al (2007) reported L4 of Hysterothylacium sp. in the haemocoel of amphipods, Paracorophium excavatum, from New Zealand waters.…”
Section: *Contracaecum Osculatum (Rudolphi 1802) Baylis 1920 (Sensumentioning
confidence: 99%